MTA: Transforming Farmers' Lives In Latin America - Hiles, Ximena; Navarro-Racines, Carlos Eduardo; Giraldo Mendez, Diana Carolina (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Local Technical Agroclimatic Comittees (MTA - due to its Spanish initials) are spaces for dialogue between a diversity of local stakeholders including scientists, technicians, representatives of the public and private sectors and farmers that seek to understand climate possible behavior in a territory and to generate recommendations to reduce risks associated with expected climate variability.